Draft Genome Sequences of Nine Strains of Brochothrix thermosphacta, Carnobacterium divergens, Lactobacillus algidus, Lactobacillus fuchuensis, Lactococcus piscium, Leuconostoc gelidum subsp. gasicomitatum, Pseudomonas lundensis, and Weissella viridescens, a Collection of Psychrotrophic Species Involved in Meat and Seafood Spoilage - Poirier, Simon (Genome Announc, 2018)
In this study, we present the draft genome sequences of nine strains from various psychrotrophic species identified in meat products and being recognized as important emerging food spoilers. Many of these species have only one or few strains being sequenced, and this work will contribute to the improvement of the overall genomic knowledge about them.